Extracorporeal membrane oxygenation (ECMO) for critically ill adults in the emergency department: history, current applications, and future directions. Issue 1 (December 2015) - Mosier, Jarrod; Kelsey, Melissa; Raz, Yuval; Gunnerson, Kyle; Meyer, Robyn; Hypes, Cameron; Malo, Josh; Whitmore, Sage; Spaite, Daniel
Abstract Extracorporeal membrane oxygenation (ECMO) is a mode of extracorporeal life support that augments oxygenation, ventilation and/or cardiac output via cannulae connected to a circuit that pumps blood through an oxygenator and back into the patient. ECMO has been used for decades to support cardiopulmonary disease refractory to conventional therapy. While not robust, there are promising data for the use of ECMO in acute hypoxemic respiratory failure, cardiac arrest, and cardiogenic shock and the potential indications for ECMO continue to increase. This review discusses the existing literature on the potential use of ECMO in critically ill patients within the emergency department.